GConsent - A Consent Ontology based on the GDPR - O'Sullivan, Declan; Lewis, David; Debruyne, Christophe (Springer, 2019)
Consent is an important legal basis for the processing of personal data under the General Data Protection Regulation (GDPR), which is the current European data protection law. GPDR provides constraints and obligations on the validity of consent, and provides data subjects with the right to withdraw their consent at any time. Determining and demonstrating compliance to these obligations require information on how the consent was obtained, used, and changed over time. Existing work demonstrates feasibility of semantic web technologies in modelling information and determining compliance for GDPR. Although these address consent, they currently do not model all the information associated with it. In this paper, we address this by first presenting our analysis of information associated with consent under the GDPR. We then present GConsent, an OWL2-DL ontology for representation of consent and its associated information such as provenance. The paper presents the methodology used in the creation and validation of the ontology as well as an example use-case demonstrating its applicability. The ontology and this paper can be accessed online at https://w3id.org/GConsent.
16th European Semantic Web Conference (ESWC)
PUBLISHED
Portoroz, Slovenia
Keywords: Consent; GDPR; Regulatory compliance; OWL2-DL ontology; Digital Engagement; Knowledge and data engineering